Correction: Long non-coding RNA SNHG17 is an unfavourable prognostic factor and promotes cell proliferation by epigenetically silencing P57 in colorectal cancer. (24th February 2020) - Ma, Zhonghua; Gu, Shengying; Song, Min; Yan, Changsheng; Hui, Bingqing; Ji, Hao; Wang, Jirong; Zhang, Jianping; Wang, Keming; Zhao, Qinghong
Abstract : Correction for 'Long non-coding RNA SNHG17 is an unfavourable prognostic factor and promotes cell proliferation by epigenetically silencing P57 in colorectal cancer' by Zhonghua Ma et al., Mol. BioSyst., 2017, 13, 2350–2361.